Carbohydrate mouth rinse counters fatigue related strength reduction - Jensen, M.; Stellingwerff, T.; Klimstra, M. (International Journal of Sport Nutrition and Exercise Metabolism, 2015)
The purpose was to determine the effect of carbohydrate (CHO) mouth rinse on maximal voluntary contraction (MVC) and neuromuscular output in a fatigued state. It was hypothesized that CHO mouth rinse would potentiate torque output in a fatigued state. In a double-blind, cross-over design, 12 competitive male athletes (9 rowers, 1 cyclist, 1 runner and 1 volleyball player) initially performed 3 × 5 s MVC isometric knee extensions followed by a 50% MVC contraction until volitional exhaustion, with quadriceps muscle activity measured via electromyography (EMG). Immediately after, either an 8% CHO maltodextrin (WASH), or noncaloric artificial sweetener (PLA) was mouth rinsed for 10sec, before 3 × 5 s final MVCs. Fatigue caused a significant decline in post fatigue MVC trial 1 for 3 s average torque (p = .03) and peak torque (p = .02) for PLA. This fatigue related decline in torque was not noticed for WASH, with a 2.5% and 3.5% less attenuation in peak and average torque, respectively in post fatigue MVC1 compared with PLA. The effect size for MVC trial 1 between WASH/PLA was seen to be small positive (ES = 0.22; 55% likelihood of positive). Overall for EMG RMS, there were no significant differences between PLA and WASH among all muscles. EMG median frequency showed comparable results between conditions with significant reductions due to fatigue. Taken together, this evidence suggests that the attenuation of torque post fatigue was less for CHO mouth rinse than a placebo. Even though the gains were marginal, these discoveries may play an important role in sport performance, as small performance effects can have significant outcomes in real-world competitions.